FIROKI’S CREATION - Tojixon Toshboltayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides information and analysis on the creative heritage of one of the representatives of the Kokan literary environment in the 20th century, the poet Dostmuhammad Alimuhammadzade Firoqi, and the ideological, artistic, and poetic features of his works.